Isolated Crohn's disease of the appendix presenting as growth delay in an adolescent male - Rachel Aber; Gal Becker; Adi Anafy; Amir Ben-Tov; Ariel Greenberg; Igor Sukhotnik (Elsevier, 2022)
The clinical diagnosis of classic Crohn's disease (CD) isolated to the appendix is based on a typical history, tender right lower quadrant fullness or mass and characteristic radiographic findings. Appendicitis may also present with chronic or recurrent symptoms, and this presentation may be confused with CD. We herein describe the case of a young teenage boy with a presumptive diagnosis of irritable bowel syndrome followed by chronic appendicitis, who underwent appendectomy and was ultimately diagnosed by histologic examination as having isolated appendiceal Crohn's disease (ACD).